Preservantes utilizados en el curado de maderas - Moreno Salinas, Alcides (2017)
The aim of this work is to know and identify the most commonly used preservants for protecting wood, by curing. Wood is a material which is susceptible to attack by agents of deterioration as insects and wood decay fungi which will degrade cellulose main component of wood. Preservants the most used are chromium, copper, arsenic, borax, varnishes, lacquers, oils, salts, oil and application techniques such as spraying, dipping, spreading, vacuum-pressure. The main types of preservants used are copper, chromium, arsenic, salts, borax, varnishes, oil and more efficient application techniques are spraying, dipping, diffusion, vacuum pressure and a more efficient is by immersion for being more economical.